Thriving in a global market technology strategies for UK civil engineering exports : report on the ICE-led project Technology Support for Civil Engineering Exports, supported by the UK Department of the Environment, Transport and the Regions under the Partners in Technology Scheme. (Institution of Civil Engineers, 1998)
'This report encourages confident and environmentally sustainable utilisation of our wealthcreating ability through technology, doing better what our forebears did in the last century. We need to use technology to engineer a harmonious future for ourselves and the rest of the environment.' - Sir Alan Cockshaw, ICE President 1997/8.